The Team Teachers' Beliefs about Their Roles in Collaborative Team Teaching in Indonesia Context - Eka Indah Nuraini (Journal of English Language Teaching and Learning (JETLE), 2022)
This study aims to report the results of qualitative research using a case study design on the team teachers’ beliefs about their roles in collaborative team teaching between native-English speaking teachers (NESTs) and local English teachers (LETs) in Indonesian secondary schools and aspects that shape their beliefs. Two pairs of English team teachers at two Junior High Schools in Ponorogo were interviewed and their classroom practices were observed. Then, the data were analyzed by using the interactive model proposed by Miles Huberman. The findings showed that NESTs and LETs possessed different beliefs about their roles in team teaching in which NESTs perceived their roles primarily dealing with linguistic and cultural aspects. Meanwhile, LETs played roles as the main teachers who led the classes by writing lesson plans, choosing the materials, focusing on theory (delivering basic materials), and assessing students. Furthermore, three factors shape teachers’ beliefs about their roles in team teaching, namely training, teaching experience, and learning experience. This research findings are expected to provide some recommendations to wide range of stakeholders to re-examine the practice of team teaching between NESTs and LETs by focusing on their respective strengths to generate the best classroom practices.